Pengaruh Good Corporate Governance dan Environmental Performance Terhadap Kinerja Keuangan Perusahaan - Adhara Sakana Qalbi; Hermi hermi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to analyze the effect of good corporate governance and environmental performance on the company's financial performance. The population of this study are non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 to 2021. Based on the criteria determined using the purposive sampling technique, a research sample of 81 companies was generated for three years. The research method used is multiple regression model. The results showed that the independent board of commissioners and institutional ownership had a positive effect on financial performance, while the audit committee and environmental performance had no effect on financial performance.